2011
DOI: 10.1002/jor.21398
|View full text |Cite
|
Sign up to set email alerts
|

Novel quinazoline HMJ‐30 induces U‐2 OS human osteogenic sarcoma cell apoptosis through induction of oxidative stress and up‐regulation of ATM/p53 signaling pathway

Abstract: Human osteogenic sarcoma is the most common primary bone tumor. Despite of the success of frontline therapy, about 40% of patients have disease progression and further therapy is palliative and toxic. In this study, we developed a novel quinazoline HMJ-30 to investigate the cell growth inhibition and apoptotic responses in U-2 OS human osteogenic sarcoma cells. Our results demonstrated that HMJ-30 significantly reduced cell viabilities of U-2 OS, HOS, and 143B cells in a dose-dependent manner, but it exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
2
42
1
Order By: Relevance
“…It was reported that ROS can modulate death receptor pathway in cancer cells (8,10). Our hypothesis showed that extrinsic death receptor pathway is a central component in kaempferol-triggered apoptosis of HUVECs.…”
Section: Atm-p53-mediated Death Receptor Pathway Is Involved In Kaempmentioning
confidence: 67%
See 2 more Smart Citations
“…It was reported that ROS can modulate death receptor pathway in cancer cells (8,10). Our hypothesis showed that extrinsic death receptor pathway is a central component in kaempferol-triggered apoptosis of HUVECs.…”
Section: Atm-p53-mediated Death Receptor Pathway Is Involved In Kaempmentioning
confidence: 67%
“…The agarose-cell mixture (50 µl) was immediately pipetted onto comet slides. The slides were then immersed in pre-chilled lysis solution for 30 min at 4˚C as previously described (10). After lysis, horizontal electrophoresis was performed for 30 min at 300 mA.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR cells (2 × 10 5 cells/per well) were plated into the 12-well plates and then treated with 100 μM of YC-1 for 0, 12, 24, 36 and 48 h. The cells were then fixed, followed by staining with propidium iodide (PI) solution as previously described [91, 92]. The cell cycle profiling and the data analysis were determined utilizing a Muse Cell Analyzer (Merck Millipore, Hayward, CA, USA) [9398].…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of pNA released from the substrate was calculated using a calibration curve prepared from defined pNA solutions. The experiments were performed in triplicate (27).…”
Section: Methodsmentioning
confidence: 99%